A method for consolidating and making a sample of loose carbonate rock
Patent Information
- Application Number
- CN202611064253.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-07-17
AI Technical Summary
[0005]鉴于此,本发明提出了一种松散碳酸盐岩样品固结制片方法,以解决现有技术中存在的样品制备精度不高的问题
本发明针对松散碳酸盐岩高孔隙、低胶结、易破碎的特性,采用“真空浸渍+双氧水液封保压+分级温压固结”一体化工艺,有效解决了现有技术中树脂渗透不充分、样品固结不牢、微观结构易失真等难题,既保障了岩样原始微观结构的保真性和薄片制备质量,满足高精度测试需求,又具备工艺稳定、可实施性强、适配范围广的优势,且全程清洁无污染,填补了松散碳酸盐岩专用固结制片的技术空白,在油气储层勘探、地质评价等相关领域具有重要实用价值和推广前景。
Smart Images

Figure CN122567349B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oil and gas development technology, specifically a method for consolidating and preparing sections of loose carbonate rock samples. Background Technology
[0002] Loose carbonate rocks are widely distributed in geological rock masses, and the quality of their thin section preparation directly determines the accuracy of research results. However, loose carbonate rocks have well-developed pores, low cementation, and a loose, easily broken structure, making it difficult for traditional thin section preparation techniques to effectively fix and shape them, which has become a major problem restricting their fine analysis and applied research.
[0003] Existing methods for preparing loose rock thin sections mainly include direct cementation, atmospheric pressure impregnation, and single thermo-compression consolidation. Direct cementation results in insufficient resin penetration, low sample consolidation strength, and easy disintegration and pore blockage during slide preparation. Atmospheric pressure impregnation lacks vacuum assistance, leading to insufficient pore degassing and poor impregnation effect. Single thermo-compression consolidation cannot achieve gradient curing, easily generating internal stress and uneven curing, making it difficult to meet the requirements of high-precision sample preparation.
[0004] Vacuum impregnation machines, VPI equipment, and traditional embedding machines are mostly used in other technical fields such as sealing and seepage prevention, insulation impregnation, and sample embedding. Their technical concepts of vacuum degassing, liquid impregnation, and curing can provide important inspiration for this invention. However, such equipment is not designed for the preparation of thin sections of loose carbonate rock samples with high porosity, low cementation, and easy breakage, and has obvious shortcomings in terms of specialization, fidelity, and process adaptability. Summary of the Invention
[0005] In view of this, the present invention proposes a method for consolidating and preparing loose carbonate rock samples to solve the problem of low sample preparation accuracy in the prior art.
[0006] This invention discloses a method for consolidating and preparing sections from loose carbonate rock samples, comprising the following steps: Step S1: Collect loose carbonate rock samples from the target area and perform cleaning, cutting, ultrasonic cleaning, and drying pretreatment in sequence; Loose carbonate rocks refer to unconsolidated or weakly consolidated carbonate sediments and rocks that are poorly cemented, loosely structured, easily broken, and have a porosity of 30%±5%. Under conventional slicing processes, they are prone to disintegration, chipping, and structural distortion, making it difficult to directly slice and polish them to prepare thin rock sections.
[0007] Step S2: Place the pretreated loose carbonate rock sample into a high-temperature and high-pressure vacuum impregnation and consolidation vessel, and evacuate the vacuum in the vessel to -0.090MPa to -0.098MPa at a rate of 1L / s to 2L / s and maintain it for 30min to 60min. Then, while maintaining the vacuum, add the injection agent dropwise at a rate of 5mL / min to 10mL / min at room temperature. Step S3: Maintain the vacuum inside the vessel, inject hydrogen peroxide sealant into the vessel and maintain the pressure for at least 30 minutes to form a stable stratified liquid seal; Step S4: Perform staged heating and pressurization to solidify the sample after liquid sealing and pressure holding; Step S5: After pressure consolidation, the sample is sequentially sliced, ground, and polished to obtain sample thin slices.
[0008] One embodiment of the present invention is that the injection agent is prepared by mixing a curing agent and a resin at a mass ratio of 1:5 to 8 and stirring for at least 5 minutes.
[0009] One embodiment of the present invention is that the resin is one of epoxy resin, methyl methacrylate, and fir resin.
[0010] Furthermore, the curing agent is one of ethylenediamine, triethanolamine, rosin, turpentine, purified paraffin, and azobisisobutyronitrile; wherein ethylenediamine and triethanolamine are used in conjunction with epoxy resin; rosin, turpentine, and purified paraffin are used in conjunction with fir resin; and azobisisobutyronitrile is used in conjunction with methyl methacrylate.
[0011] In one embodiment of the present invention, the injection volume of the injectant is 2 to 3 times the sample volume.
[0012] In one embodiment of the present invention, the hydrogen peroxide sealant described in step S3 is added dropwise to the vessel at a rate of 2 mL / min to 10 mL / min at room temperature until a liquid seal layer with a thickness of 10 mm to 20 mm is formed above the sample.
[0013] One embodiment of the present invention is that the specific method for staged heating and pressurization consolidation in step S4 is as follows: Step S41: Raise the temperature inside the reactor to 65℃±2℃ at a rate of 2℃ / min~5℃ / min, and adjust the pressure inside the reactor to 10MPa~15MPa±0.5MPa. Maintain the temperature and pressure for 4 hours to complete the first-stage consolidation. Step S42: Raise the temperature inside the vessel to 95℃±2℃ at the same rate, and raise the pressure inside the vessel to 20MPa~30MPa±0.5MPa. Maintain the temperature and pressure for 6 hours to complete the secondary consolidation. Step S43: Cool to room temperature at a rate of 3℃ / min to 5℃ / min, and slowly depressurize to atmospheric pressure to obtain the pressurized and consolidated rock sample.
[0014] In one embodiment of the present invention, the thickness of the sample sheet in step S5 is 30 μm to 50 μm ± 5 μm.
[0015] One embodiment of the present invention comprises a high-temperature and high-pressure vacuum impregnation and consolidation reactor including a base, an equipment frame, a pressure vessel, and a sample chamber, wherein: The rectangular frame-shaped equipment rack is connected to the base, and the base is equipped with an adjustable lifting seat and a pressure vessel from bottom to top; The pressure vessel is a metal barrel with a lid on top. The top frame of the equipment is equipped with a safety valve, a liquid injection pipe, an exhaust pipe, an air inlet pipe, and a pressure pump. The safety valve, liquid injection pipe, exhaust pipe, and air inlet pipe are connected to the inside of the pressure vessel through the cover pipe. The pressure pump delivers gas through the exhaust pipe and air inlet pipe to control the internal pressure of the pressure vessel. A sample stage is located at the center of the bottom surface of the pressure vessel. A heating device and an insulation layer are also installed on the inner side of the pressure vessel. A sample chamber is installed on the sample stage to hold the pretreated loose carbonate rock sample. The injection tube extends into the sample chamber.
[0016] The technical advantages of this invention are as follows: This invention addresses the characteristics of loose carbonate rocks, such as high porosity, low cementation, and fragility, by employing an integrated process of "vacuum impregnation + hydrogen peroxide liquid sealing and pressure holding + staged temperature and pressure consolidation." This effectively solves the problems of insufficient resin penetration, weak sample consolidation, and easy distortion of microstructure in existing technologies. It not only ensures the fidelity of the original microstructure of the rock sample and the quality of thin section preparation, meeting the requirements of high-precision testing, but also has the advantages of stable process, strong feasibility, and wide applicability. Moreover, the entire process is clean and pollution-free, filling the technical gap in the consolidation and section preparation of loose carbonate rocks. It has important practical value and promising prospects for promotion in oil and gas reservoir exploration, geological evaluation, and other related fields. Attached Figure Description
[0017] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained from these drawings without creative effort.
[0018] Figure 1 This is an overall flowchart of the present invention; Figure 2 This is a schematic diagram of the high-temperature and high-pressure vacuum impregnation and consolidation reactor in this invention; In the diagram, 1-base, 2-equipment rack, 3-pressure vessel, 4-safety valve, 5-liquid injection pipe, 6-exhaust pipe, 7-air inlet pipe, 8-pressure pump, 9-heating device, 10-insulation layer, 11-sample chamber, 12-sample stage, 13-lifting seat. Detailed Implementation
[0019] The present invention will be further described in detail below with reference to the embodiments. However, the implementation of the present invention is not limited thereto. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the materials and reagents used are commercially available unless otherwise specified.
[0020] Example This embodiment selects loose carbonate rock samples from the Oligocene strata in a certain area of the South China Sea. Figure 1 The prepared slides are prepared using the slide preparation process shown. This rock sample has well-developed pores, low cementation, and is easily broken. Conventional slide preparation methods are prone to disintegration and pore blockage. Therefore, the consolidation slide preparation method of this invention is used for slide preparation. Step S1: Collect loose carbonate rock samples from the target area and perform cleaning, cutting, ultrasonic cleaning, and drying pretreatment in sequence; First, the Oligocene loose carbonate rock samples collected from a certain area of the South China Sea were pre-processed. The mud, sand and rock debris attached to the surface of the rock samples were manually cleaned. The rock samples were then cut into 2cm×2cm×2cm samples to be processed using a rock cutting machine to avoid the rock samples being too large and causing insufficient impregnation in the subsequent process. The sample was then cleaned and dried using a step-by-step cleaning-constant temperature drying method. The ultrasonic power was controlled at 300W-400W and the ultrasonic time was 5-8 minutes per cycle. First, the sample was ultrasonically cleaned once with deionized water to remove soluble impurities, and then ultrasonically cleaned once with analytical grade ethanol to remove oil stains. The cleaning intensity was controlled throughout the process to prevent damage to the original rock sample. The constant temperature drying temperature was 60℃-80℃, and the sample was dried until the sample quality was constant.
[0021] In this embodiment, the sample was placed in deionized water, and ultrasonic cleaning was performed once with a power of 350W and a time of 6 minutes to remove soluble impurities from the pores of the sample. The sample was then placed in analytical grade ethanol and ultrasonically cleaned once with the same parameters to remove oil stains from the sample surface and pores. The cleaning intensity was controlled throughout the process to prevent damage to the loose rock sample structure. After cleaning, the sample was placed in a 70°C constant temperature drying oven to dry until the mass was constant. After being removed, the sample was placed in a desiccator for later use to prevent the sample from absorbing moisture again.
[0022] Simultaneously, the injection agent and sealant are prepared: The injection agent is prepared by mixing the curing agent and resin at a mass ratio of 1:5 to 8 and stirring for at least 5 minutes. In this embodiment, the injection agent is mixed with the resin and curing agent at a mass ratio of 6:1 and stirred for 6 minutes using a magnetic stirrer to ensure that the resin and curing agent are mixed evenly. After standing to defoam, it is ready for use. This ratio can take into account both the penetration performance of the injection agent and the subsequent solidification strength. The sealant is hydrogen peroxide, which is immiscible with the injection agent and has a density difference. It is clean, pollution-free, and has no safety hazards, meeting the process requirements of liquid sealing and pressure holding.
[0023] Step S2: Place the pretreated loose carbonate rock sample into a high-temperature and high-pressure vacuum impregnation and consolidation vessel, and evacuate the vacuum in the vessel to -0.090MPa to -0.098MPa at a rate of 1L / s to 2L / s and maintain it for 30min to 60min. Then, while maintaining the vacuum, add the injection agent dropwise at a rate of 5mL / min to 10mL / min at room temperature. The pretreated and dried loose carbonate rock sample was placed in... Figure 2 In the sample chamber 11 of the high-temperature and high-pressure vacuum impregnation and consolidation vessel shown, the pressure vessel 3 is closed and sealed, and the lifting seat 13 is adjusted to control the pressure vessel 3 in a suitable position; the pressure pump 8 is started, and vacuum treatment is performed through the exhaust pipe 6 of the vessel body. The vacuum rate is set to 1.5L / s, and the vacuum degree in the vessel body is maintained at -0.095MPa for 45 minutes to fully remove the air in the sample pores and provide conditions for the injection agent to permeate.
[0024] After vacuum pressure holding is completed, the vacuum state is maintained, and the prepared injection agent is slowly added dropwise at a rate of 8 mL / min through the injection tube 5 of the pressure vessel 3. The injection agent is a low viscosity bisphenol A epoxy resin and ethylenediamine in a mass ratio of 6:1. The injection volume can be 2 to 3 times the sample volume. In this embodiment, the injection volume is 2.5 times the sample volume to ensure that the injection agent completely covers the sample and allows the injection agent to fully penetrate into all pores inside the sample under vacuum negative pressure, completing the initial reinforcement of the sample skeleton. The entire process is kept under vacuum to avoid air entering and affecting the impregnation effect.
[0025] Step S3: Maintain the vacuum inside the vessel, inject hydrogen peroxide sealant into the vessel and maintain the pressure for at least 30 minutes to form a stable layered liquid seal on the surface of the injected agent; After the impregnation with the injection agent is completed, the vacuum state inside the vessel is maintained at -0.095MPa. Hydrogen peroxide sealant is slowly injected into the vessel at a rate of 6mL / min through the injection tube 5 at room temperature. Taking advantage of the density difference between hydrogen peroxide and the injection agent, the sealant spreads naturally on the surface of the injection agent and forms a stable 10mm layered liquid seal structure, completely covering the surface of the injection agent. The vacuum degree inside the vessel is monitored in real time by the vacuum monitoring device built into the pressure vessel 3 to maintain a stable vacuum environment throughout the process. If the vacuum degree fluctuation is detected, a small amount of sealant is added as needed, and the sealing performance of each sealing interface of the vessel is checked to ensure that no gas enters the sample pores. The liquid seal pressure is maintained for 30 minutes to ensure that the injection agent further penetrates into the micropores of the sample and improves the impregnation effect.
[0026] Step S4: Perform staged heating and pressurization to solidify the sample after liquid sealing and pressure holding; After the liquid sealing and pressure holding is completed, the vessel body is kept sealed. The sample is directly subjected to graded heating and pressure consolidation treatment in the high temperature and high pressure vacuum impregnation and consolidation vessel. The sample is not transferred throughout the process to avoid damage to the sample structure. The specific method for staged heating and pressurization consolidation is as follows: Step S41: Raise the temperature inside the reactor to 65℃±2℃ at a rate of 2℃ / min~5℃ / min, and adjust the pressure inside the reactor to 10MPa~15MPa±0.5MPa. Maintain the temperature and pressure for 4 hours to complete the first-stage consolidation. Step S42: Raise the temperature inside the vessel to 95℃±2℃ at the same rate, and raise the pressure inside the vessel to 20MPa~30MPa±0.5MPa. Maintain the temperature and pressure for 6 hours to complete the secondary consolidation. Step S43: Cool to room temperature at a rate of 3℃ / min to 5℃ / min, and slowly depressurize to atmospheric pressure to obtain the pressurized and consolidated rock sample.
[0027] In this embodiment, the heating rate is set to 3℃ / min in the first stage of consolidation to raise the temperature inside the vessel to 65℃±2℃. At the same time, the pressure inside the vessel is increased to 12MPa±0.5MPa through the air inlet pipe 7. After reaching the parameters, the temperature and pressure are maintained for 4 hours to allow the injected agent to initially solidify, fix the loose skeleton of the sample, and prevent the sample structure from deforming during the subsequent pressure and temperature increase process. The heating operation is mainly performed by the heating device 9. The insulation layer 10 prevents heat loss and provides an insulating environment. The heating device 9 can be connected to the outside of the pressure vessel 3, including but not limited to heating equipment in the form of heating wires, heating tubes, etc.
[0028] After the first stage of consolidation is completed, the temperature inside the reactor is raised to 95℃±2℃ at a heating rate of 3℃ / min, and the pressure is raised to 25MPa±0.5MPa simultaneously. After reaching the parameters, the temperature and pressure are maintained for 6 hours to allow the injected agent to fully cross-link and solidify. After consolidation is completed, the cooling rate is set to 4℃ / min to allow the temperature inside the reactor to drop naturally to room temperature, and then the pressure is slowly released to atmospheric pressure. Finally, a loose carbonate rock sample with complete consolidation, qualified strength and intact original microstructure is obtained.
[0029] Step S5: After pressure consolidation, the sample is sequentially sliced, ground, and polished to obtain sample thin slices.
[0030] The rock sample was sliced into 0.5 mm thick slices using a diamond slicer. The grinding process employed a gradient grinding method, using 400-grit, 800-grit, and 1200-grit diamond sandpaper for dry grinding. Each sandpaper was replaced after the surface of the rock slice was smooth and free of scratches. The polishing time was 10 to 15 minutes until a mirror-like effect was achieved on the surface of the slice. The final thickness of the sample slices should be 30 μm to 50 μm ± 5 μm.
[0031] In this embodiment, the consolidated rock sample is taken out and cut into 0.5mm thick rock slices using a diamond slicer to remove burrs and debris generated during the cutting process. Then, the sample is ground using a gradient polishing method, with 400-grit, 800-grit, and 1200-grit diamond sandpaper used for dry grinding in sequence. Each sandpaper is replaced with the next level of sandpaper after the surface of the rock slice is smooth and free of scratches. After grinding, the rock slices are polished for 12 minutes until a mirror-like finish is achieved on the surface.
[0032] The prepared thin sections were subjected to quality inspection. The thickness of the thin sections was measured using a thin section thickness gauge, and the final thickness of the thin sections was controlled to be 40 μm with a thickness deviation of no more than ±5 μm. The microstructure of the thin sections was observed using a polarizing microscope to confirm that there was no disintegration, chipping, or pore blockage, and that the original pore structure and mineral composition of the rock sample were intact. The qualified thin sections can be directly used for microscopic observation, component analysis, and testing of oil and gas reservoir-related parameters.
[0033] Comparative Test To verify the technical effectiveness of the hydrogen peroxide liquid sealing and pressure maintenance and two-stage gradient temperature and pressure consolidation process described in this invention, loose carbonate rock samples with the same core location, porosity of 30% ± 5%, and degree of cementation as those in the examples were selected and parallel experiments were conducted as a comparative example. All samples were 2cm × 2cm × 2cm in size, and the pretreatment and vacuum impregnation processes were completely consistent with those in the examples, with only the sealing method and consolidation process being changed.
[0034] Comparative Example 1: Ordinary oil sealing + single high temperature and high pressure consolidation was adopted. The consolidation conditions were 95℃, 25MPa, and heat and pressure holding for 10h. The rest of the process was completely consistent with the experimental group.
[0035] Comparative Example 2: Ordinary machine oil sealing + room temperature and pressure curing was used. The curing conditions were room temperature (25℃) and normal pressure, and the curing time was 10 hours. The rest of the process was completely the same as the experimental group.
[0036] The tests listed in Table 1 were performed to compare the preparation effects of the examples and the comparative examples. The specific results are shown in Table 1. Table 1. Comparison of the sheet preparation effects of rock samples with different sealing methods and consolidation processes. As shown in Table 1, the present invention uses hydrogen peroxide as a liquid sealant, which significantly improves pressure holding stability compared to ordinary engine oil sealant, eliminates pore contamination, and has a high original pore retention rate. The main reason for this effect is likely based on the following characteristics of hydrogen peroxide: (1) Hydrogen peroxide is a polar solution with high surface tension. It has poor wettability on carbonate rocks and cannot be absorbed by pores, thus achieving zero pore contamination and a primary pore retention rate of ≥96%. (2) Hydrogen peroxide has low volatility and does not release gas under high vacuum at room temperature. It can form a stable liquid seal layer with vacuum fluctuation ≤ ±0.002MPa. Although there is a trace amount of decomposition in the later high temperature and high pressure stage, the product is harmless, produces gas under high pressure, and does not pollute the rock sample. It is more temperature and pressure resistant and cleaner than engine oil. (3) Hydrogen peroxide is completely immiscible with organic resin, with a clear interface, does not contaminate the resin system, does not affect the resin curing process, and avoids internal stress defects in the solidified body.
[0037] Meanwhile, this invention employs a two-stage gradient temperature-pressure consolidation process. Compared to single high-temperature-high-pressure or single-temperature-normal-pressure consolidation, this effectively releases internal stress, avoids microcracks in the rock sample, and balances consolidation strength with the fidelity of the microstructure. The synergistic effect of these two processes ensures that the consolidated rock sample meets the requirements for thin section preparation, achieving a thin section qualification rate of 98%, significantly better than the comparative groups. This effectively solves the technical problems of easy disintegration, structural distortion, and insufficient resin penetration in loose carbonate rock sections, fully demonstrating the superiority of this invention.
[0038] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the embodiments of the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be defined by the scope of the claims.
Claims
1. A method for consolidating and preparing sections from loose carbonate rock samples, characterized in that, Includes the following steps: Step S1: Collect loose carbonate rock samples from the target area and perform cleaning, cutting, ultrasonic cleaning, and drying pretreatment in sequence; Step S2: Place the pretreated loose carbonate rock sample into a high-temperature and high-pressure vacuum impregnation and consolidation vessel, and evacuate the vacuum in the vessel to -0.090MPa to -0.098MPa at a rate of 1L / s to 2L / s and maintain it for 30min to 60min. Then, while maintaining the vacuum, add the injection agent dropwise at a rate of 5mL / min to 10mL / min at room temperature. Step S3: Maintain the vacuum inside the vessel, inject hydrogen peroxide sealant into the vessel and maintain the pressure for at least 30 minutes to form a stable stratified liquid seal; Step S4: Perform staged heating and pressurization to solidify the sample after liquid sealing and pressure holding; Step S5: After pressure consolidation, the sample is sequentially sliced, ground, and polished to obtain sample thin slices; The specific method for staged heating and pressurization consolidation in step S4 is as follows: Step S41: Raise the temperature inside the reactor to 65℃±2℃ at a rate of 2℃ / min~5℃ / min, and adjust the pressure inside the reactor to 10MPa~15MPa. Maintain the temperature and pressure for 4 hours to complete the first-stage consolidation. Step S42: Raise the temperature inside the vessel to 95℃±2℃ at the same rate, raise the pressure inside the vessel to 20MPa~30MPa, and maintain the temperature and pressure for 6 hours to complete the secondary consolidation; Step S43: Cool to room temperature at a rate of 3℃ / min to 5℃ / min, and slowly depressurize to atmospheric pressure to obtain the pressurized and consolidated rock sample.
2. The method for consolidating and preparing sections from loose carbonate rock samples according to claim 1, characterized in that: The injection agent is prepared by mixing a curing agent and a resin at a mass ratio of 1:5 to 8 and stirring for at least 5 minutes.
3. The method for consolidating and preparing sections from loose carbonate rock samples according to claim 2, characterized in that: The resin is one of epoxy resin, methyl methacrylate, and fir resin.
4. The method for consolidating and preparing sections from loose carbonate rock samples according to claim 3, characterized in that: The curing agent is one of ethylenediamine, triethanolamine, rosin, turpentine, purified paraffin, and azobisisobutyronitrile; wherein ethylenediamine or triethanolamine is used in conjunction with epoxy resin; rosin, turpentine, or purified paraffin is used in conjunction with fir resin; and azobisisobutyronitrile is used in conjunction with methyl methacrylate.
5. The method for consolidating and preparing sections from loose carbonate rock samples according to claim 1, characterized in that: The injection volume of the injectant is 2 to 3 times the sample volume.
6. The method for consolidating and preparing sections from loose carbonate rock samples according to claim 1, characterized in that: In step S3, the hydrogen peroxide sealant is added to the vessel at a rate of 2 mL / min to 10 mL / min at room temperature until a liquid seal layer with a thickness of 10 mm to 20 mm is formed above the sample.
7. The method for consolidating and preparing sections from loose carbonate rock samples according to claim 1, characterized in that: The thickness of the sample sheet in step S5 is 30 μm to 50 μm.
8. The method for consolidating and preparing sections from loose carbonate rock samples according to claim 1, characterized in that: The high-temperature and high-pressure vacuum impregnation and consolidation reactor includes a base (1), an equipment frame (2), a pressure vessel (3), and a sample chamber (11), wherein: The rectangular frame-shaped equipment rack (2) is connected to the base (1). The base (1) is provided with a height-adjustable lifting seat (13) and a pressure vessel (3) from bottom to top. The pressure vessel (3) is a metal barrel with a lid on top. The top frame of the equipment rack (2) is equipped with a safety valve (4), a liquid injection pipe (5), an exhaust pipe (6), an air inlet pipe (7), and a pressure pump (8). The safety valve (4), liquid injection pipe (5), exhaust pipe (6), and air inlet pipe (7) are connected to the inside of the pressure vessel (3) through the cover pipe. The pressure pump (8) delivers gas through the exhaust pipe (6) or the air inlet pipe (7) to control the internal pressure of the pressure vessel (3). A sample stage (12) is provided at the center of the bottom surface of the pressure vessel (3). A heating device (9) and a heat insulation layer (10) are also provided on the inner side of the pressure vessel (3). A sample chamber (11) is provided on the sample stage (12) to hold the pretreated loose carbonate rock sample. The injection pipe (5) extends into the sample chamber (11).
Citation Information
Patent Citations
Rock casting sheet die-casting preparation method
CN111157310A